2022
DOI: 10.3390/en15072591
|View full text |Cite
|
Sign up to set email alerts
|

Waste Mandarin Peel as an Eco-Friendly Water-Based Drilling Fluid Additive

Abstract: Drilling fluid represents the most important fluid that must fulfill numerous important assignments during drilling operations. Many commercially available additives for water-based drilling fluid fall into the category of non-degradable and environmentally hazardous materials. Significant development in this area can be made by using biodegradable materials as additives in drilling fluids. The objective of this study was to determine whether mandarin peel powder particle size affects the properties of the dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A comparison of three additives including raw welding waste, welding waste-derived GO and Both additives were able to form the thinner mud cake compared with the conventional WBDF. From this study, it can be concluded that waste-derived GO can prominently improve the filtration properties of WBDF [49,50].…”
Section: Discussionmentioning
confidence: 64%
“…A comparison of three additives including raw welding waste, welding waste-derived GO and Both additives were able to form the thinner mud cake compared with the conventional WBDF. From this study, it can be concluded that waste-derived GO can prominently improve the filtration properties of WBDF [49,50].…”
Section: Discussionmentioning
confidence: 64%
“…As one of the world’s major energy sources, oil is important for modern industrial development. With the increasing demand for energy and the development of oil drilling technology, deep and ultradeep wells have become important directions for drilling development. In the process of developing deep well oil and gas resources, wellbore instability is a common drilling accident problem in deep well drilling operations, which has seriously affected the exploration process of oilfield resources. , During the drilling process, shale inhibitors, filtration agents, and other additives are usually added to drilling fluids to prevent drilling safety accidents such as collapse, sticking, leakage, and blowout. …”
Section: Introductionmentioning
confidence: 99%
“…As one of the world's major energy sources, oil is important for modern industrial development. With the increasing demand for energy and the development of oil drilling technology, deep and ultra deep wells have become important directions for drilling development [1][2][3]. In the process of developing deep well oil and gas resources, wellbore instability is a common drilling accident problem in deep well drilling operations, which has seriously affected the exploration process of oil eld resources [4,5].…”
Section: Introductionmentioning
confidence: 99%